Short and medium-term effects of an education self-management program for individuals with osteoarthritis of the knee, designed and delivered by health professionals: a quality assurance study - Coleman, Sophie; Briffa, Kathy; Conroy, H.; Prince, R.; Carroll, G.; McQuade, J. (Biomed Central, 2008)
Background: Self-management (SM) programs are effective for some chronic conditions, however the evidence for arthritis SM is inconclusive. The aim of this case series project was to determine whether a newly developed specific self-management program for people with osteoarthritis of the knee (OAK), implemented by health professionals could achieve and maintain clinically meaningful improvements. Methods: Participants: 79 participants enrolled; mean age 66, with established osteoarthritis of the knee. People with coexisting inflammatory joint disease or serious co-morbidities were excluded. Intervention: 6-week disease (OA) and site (knee) specific self-management education program that included disease education, exercise advice, information on healthy lifestyle and relevant information within the constructs of self-management. This program was conducted in a community health care setting and was delivered by health professionals thereby utilising their knowledge and expertise. Measurements: Pain, physical function and mental health scales were assessed at baseline, 8 weeks, 6 and 12 months using WOMAC and SF-36 questionnaires. Changes in pain during the 8-week intervention phase were monitored with VAS. Results: Pain improved during the intervention phase: mean (95% CI) change 15 (8 to 22) mm. Improvements (0.3 to 0.5 standard deviation units) in indices of pain, mental health and physical functioning, assessed by SF-36 and WOMAC questionnaires were demonstrated from baseline to 12 months. Conclusion: This disease and site-specific self-management education program improved health status of people with osteoarthritis of the knee in the short and medium term.